Mendeteksi Orisinalitas Hasil Scan Citra Ijazah Menerapkan Metode Blake - Robert Laia (Journal of Informatics Management and Information Technology, 2021)
The rapid development of technology now causes frequent abuse of computer performance systems which are widely used as one of the crimes of manipulating document files that harm others. it can be known whether the file is original or not if the results are the same then the file is said to be original, and if the results are not the same then the file is said to be not original. original and non-original files